Collectivist Discourses in Relational Intersectionality: Insights from Chinese American Christian Couples. (November 2021) - Quek, Karen Mui-Teng; Hsieh, Natalie Wei-Mun; Eppler, Christie
Intersectionality espouses progressive societal dominant discourse norms that describe persons as individuals connected to a variety of social locations (e.g., gender, socioeconomic status [SES], ethnicity, sexual orientation, spirituality, vocation). This may not resonate with the cultural ideals of collectivist and bicultural communities, who are better understood when considered in context of both dominant and local intersectionality discourses. This retrospective interpretive thematic analysis examines the lived experiences of Chinese American Christian couples as they negotiate identity and roles in early parenthood. Findings indicate that the intersection of collectivist group identity markers, cultural values and spirituality guides how partners understand identity and negotiate relationship roles in marriage. Couples' varied responses to cross-cultural and dominant discourse norms and other social location factors (e.g., vocation and SES) also account for individual differences. Implications for Chinese American Christian couples, and for the application of intersectionality theory to diverse populations, are discussed.